Triage of the Wildlife Patient - Hoggard, Cheryl (Wildlife Rehabilitation Bulletin, 2017)
Treating wildlife patients necessitates a unique approach and a different set of practices than is normally set forth for companion animals. The physiological stress placed on wildlife patients—simply while doing a physical examination—can be enough to cause cardiac arrest (Bewig and Mitchell 2009). Knowing how to address an individual patient’s injuries and the time necessary for that animal to recover from each episode of human contact is essential to successful patient triage. Each wild animal brought in for help constitutes an emergency. Triage may entail rapid patient assessment, or may involve several animals, all needing medical attention immediately. Deciding which patient to treat first, how much human interaction that individual can tolerate for a given procedure, and when to stop, often determines the potential for patient survival and release.